ANALISIS KEBUTUHAN E-MODUL BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI DINAMIKA ROTASI DAN KESETIMBANGAN BENDA TEGAR - Safitri, Dini; Emiliannur, Emiliannur (Universitas Negeri Malang, 2025)
This study aims to analyze the need for developing an e-module based on Problem Based Learning as an effort to improve students' critical thinking skills in the Rotational Dynamics and Equilibrium of Rigid Objects material. The needs analysis was carried out based on the results of the initial test of critical thinking skills of grade XI students at SMAN 1 Sungai Aur which showed an average value of 37.62%, categorized as low. In addition, the results of observations and interviews showed limitations in the availability of contextual teaching materials and minimal use of digital technology in the physics learning process. These findings indicate the need to develop innovative teaching materials that can facilitate active learning and encourage student involvement in problem solving. Therefore, an e-module based on Problem Based Learning was designed which is packaged in a flipbook format through the Heyzine platform, containing elements of text, images, animations, and videos to support visual understanding of concepts. This e-module is structured by integrating Problem Based Learning syntax to build a learning environment that stimulates critical thinking skills. The results of this needs analysis stage are the basis for developing e-modules in the next stage and are expected to support more effective and meaningful physics learning.